Explanation of Teachers' Difficulties in Learning PJOK Via Online in the Era of the Covid-19 Pandemic - Arnaz Anggoro Saputro (Universitas Majalengka, 2023)
The world of education is currently facing quite complex problems due to the spread of the corona virus or commonly known as Covid-19. Therefore, the government has issued various policies to prevent the spread of this disease, one of which is the policy issued by the Minister of Education and Culture Number 4 of 2020 which regulates the process of teaching and learning at home, namely online/distance learning. This study aims to describe teacher difficulties in learning PJOK via online in the era of the co-19 pandemic. The method used in this research is descriptive qualitative. Data collection techniques using interviews and documentation. The results of the study show that teachers experience difficulties in planning, implementing, and evaluating. The difficulties faced by teachers are: (1) Difficulties in choosing the type of assessment; (2) Difficulties in explaining material (3) Difficulties in evaluating students.